Graph-Theoretic Concepts in Computer Science 38th International Workshop, WG 2012, Jerusalem, Israel, June 26-28, 2012, Revised Selcted Papers - Golumbic, Martin Charles; Stern, Michal; Levy, Avivit; Morgenstern, Gila.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed proceedings of the 38th International Workshop on Graph Theoretic Concepts in Computer Science (WG 2012) held in Jerusalem, Israel on June 26-28, 2012. The 29 revised full papers presented were carefully selected and reviewed from 78 submissions. The papers are solicited describing original results on all aspects of graph-theoretic concepts in Computer Science, e.g. structural graph theory, sequential, parallel, randomized, parameterized, and distributed graph and network algorithms and their complexity, graph grammars and graph rewriting systems, graph-based modeling, graph-drawing and layout, random graphs, diagram methods, and support of these concepts by suitable implementations. The scope of WG includes all applications of graph-theoretic concepts in Computer Science, including data structures, data bases, programming languages, computational geometry, tools for software construction, communications, computing on the web, models of the web and scale-free networks, mobile computing, concurrency, computer architectures, VLSI, artificial intelligence, graphics, CAD, operations research, and pattern recognition.
Account on Intervals -- Constructing Resilient Structures in Graphs: Rigid vs. Competitive Fault-Tolerance -- Alternating Reachabillity and Integer Sum of Closed Alternating Trails: The 3rd Annual Uri N. Peled Memorial Lecture -- Triangulation and Clique Separator Decomposition of Claw-Free Graphs -- Minimum Weighted Clique Cover on Strip-Composed Perfect Graphs -- Graph Isomorphism for Graph Classes Characterized by Two Forbidden Induced Subgraphs -- h-Quasi Planar Drawings of Bounded Treewidth Graphs in Linear Area -- The Duals of Upward Planar Graphs on Cylinders -- On the Minimum Degree Up to Local Complementation: Bounds and Complexity -- Bisections above Tight Lower Bounds -- Multi-rooted Greedy Approximation of Directed Steiner Trees with Applications -- Hydras: Directed Hypergraphs and Horn Formulas -- Bend-Bounded Path Intersection Graphs: Sausages, Noodles, and Waffles on a Grill -- Maximum Induced Multicliques and Complete Multipartite Subgraphs in Polygon-Circle Graphs and Circle Graphs -- Parameterized Domination in Circle Graphs -- On the Parameterized Complexity of Finding Separators with Non-hereditary Properties.
Keywords: Computer science; Data structures (Computer science).; Algorithms; Computer science -- Mathematics; Artificial intelligence; Geometry; Computer Science; Discrete Mathematics in Computer Science; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Data Structures; Geometry; Algorithms; Electronic books